15歳男子の下顎骨に生じた原発型エナメル上皮癌の1例 - 阿部, 亜希; 水城, 春美; 阿部, 亮輔; 八木, 正篤; 武田, 泰典; 齋藤, 大嗣 (日本口腔外科学会雑誌, 2015)
A case of primary ameloblastic carcinoma of the mandible is reported. The patient was a 15-year-old boy with a complaint of swelling of the gingiva adjacent to the lower left canine. He visited our department to receive further examination of the lesion. A bone-like hard swelling was detected in the area from the buccal gingiva adjacent to the lower left canine to the mucobuccal fold. On the basis of the results of biopsy, an ameloblastic carcinoma was diagnosed. After confirming the absence of systemic metastasis, we performed a segmental mandibulectomy with metal plate reconstruction with the patient under general anesthesia in May 2013. The diagnosis of primary ameloblastic carcinoma was confirmed on examination of the excised specimen. After 1-year follow-up, titanium mesh-assisted autogenous iliac bone grafting was performed to reconstruct the mandible in March 2014. One year 8 months have elapsed since the initial surgery. The patient has made satisfactory progress, with no signs of recurrence or metastasis.